Zalety i wady realizacji strategii marki lokalnej przez inwestorów francuskich w Polsce - wyniki badań empirycznych - Grębosz, Magdalena (Wydawnictwo Politechniki Łódzkiej, 2010)
W artykule poruszona została problematyka zarządzania markami lokalnymi przez inwestorów francuskich w Polsce. Przedstawiono zalety i wady realizacji strategii marki lokalnej przez inwestora zagranicznego w Polsce. Przeanalizowane zostały także zależności pomiędzy sposobem pozyskania marki lokalnej oraz rodzajem marki lokalnej a zaletami i wadami jej realizacji przez firmę zagraniczną na rynku polskim. W artykule przedstawione zostały wyniki badań empirycznych przeprowadzonych w 2009 i 2010 roku wśród firm francuskich posiadających w Polsce marki lokalne.

The paper presents the issue of local brand management by French investors in Poland. The process of internationalization implies a number of questions connected with brand management. Choice of the method of brand internationalization is an important issue. In the paper, the advantages and disadvantages of local brand strategy realization by foreign investor are described. The relationships between the method of local brand acquiring, type of brand and the advantages and disadvantages of its implementation by foreign companies on the Polish market are also analysed. This paper presents the results of empirical studies conducted in 2009 and 2010, in Poland among French companies with local brands in brand portfolio.
The advantages and disadvantages of local brands strategy implementation by French investors in Poland - the results of empirical studies